Clarification of Pomegranate Juice Using PSF Microfiltration Membranes Fabricated With Nano TiO2and Al2O3 - Severcan, Solmaz Sebnem; Uzal, Nigmet; Kahraman, Kevser (Wiley, 2020)
Microfiltration (MF) membranes were fabricated using PSF/PEI (17/2 wt%) with TiO(2)and Al(2)O(3)nanoparticles to enhance pomegranate juice clarification performance. The membrane performances were tested using dead-end filtration system. Membranes were characterized by Scanning Electron Microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), porosity, water contact angle, and pure water flux experiments. All MF membranes had higher porosity, pure water flux, and hydrophilicity.SEMimages of the membranes proved the nanoparticle incorporation to the PSF/PEI matrix. The quality of clarified pomegranate juice samples using PSF/PEI nanocomposite membranes were better than that of clarified using both commercial and unmodified membranes. The highest performance for the clarification of pomegranate juice samples was obtained for 0.05% of Al(2)O(3)incorporated PSF/PEI membranes with the highest color (5,781 +/- 4 PtCo), total soluble solid (16.2 +/- 0.0 Brix), total phenolic content (2,642.1 +/- 46.4 mg GAE/L), antioxidant activity (ABTS: 62.4 +/- 0.2 TEAC/L, DPPH: 41.3 +/- 0.0 TEAC/L) and total monomeric anthocyanin (100.7 +/- 1.7 mg/L). Practical applications Utilization of membrane technology in food industry has been increased rapidly in the past two decades. Due to their advantage in terms of saving color pigments, MF membranes are more suitable than UF ones for clarification of pomegranate juice. Incorporation of nanoparticles to the membrane matrix is one of the methods to increase the antifouling character and the strength of the membranes modified with hydrophilic polymers. There are some studies investigating the effect of TiO(2)and Al(2)O(3)nanoparticles on the properties of polymeric membranes. However, there are no reported data on the utilization of TiO(2)and Al(2)O(3)nanocomposite membranes for clarifying pomegranate juice. In this study, TiO(2)and Al(2)O(3)incorporated new generation PSF/PEI membranes were utilized in the clarification process of pomegranate juice for the first time in the literature. The results showed that Al(2)O(3)incorporation seems to be a good alternative for clarifying pomegranate juice with enhanced quality parameters.
Kahraman, Kevser/0000-0002-2786-3944